1995
DOI: 10.1177/026765919501000405
|View full text |Cite
|
Sign up to set email alerts
|

Influence of different flow modi during extracorporeal circulation on endothelial-derived vasoactive substances

Abstract: Influences of shear stress on endothelin (ET) as well as prostacyclin (PGF) levels are common findings in different experimental settings. Thus, plasma levels of both substances seem to be a good tool to verify if different flow modi can be produced in blood vessels by generating pulsatile flow with a roller pump. In the present study, 20 patients scheduled for elective aortocoronary bypass operation were divided into two groups at random. One group was perfused with nonpulsatile (CON-group) and the other with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0
1

Year Published

1997
1997
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 24 publications
1
11
0
1
Order By: Relevance
“…Again, studies on endothelial activation following pulsatile and non-pulsatile perfusion have given contradictory results in the current literature [11][12][13][14]; some studies reported beneficial effects of pulsatile perfusion on endothelial response to CPB [12][13][14], others did not find any superiority of pulsatile CPB over nonpulsatile perfusion [11]. Despite IABP-induced pulsatile perfusion being first suggested by Pappas and co-workers in 1975 [15], literature lacks studies analyzing the endothelial response and the cytokine release following this type of perfusion or standard linear CPB.…”
Section: Introductionmentioning
confidence: 95%
See 1 more Smart Citation
“…Again, studies on endothelial activation following pulsatile and non-pulsatile perfusion have given contradictory results in the current literature [11][12][13][14]; some studies reported beneficial effects of pulsatile perfusion on endothelial response to CPB [12][13][14], others did not find any superiority of pulsatile CPB over nonpulsatile perfusion [11]. Despite IABP-induced pulsatile perfusion being first suggested by Pappas and co-workers in 1975 [15], literature lacks studies analyzing the endothelial response and the cytokine release following this type of perfusion or standard linear CPB.…”
Section: Introductionmentioning
confidence: 95%
“…However, pulsatile CPB still represents an open question: some studies have reported beneficial effects on microcirculation, metabolism, and organ functions [3,4], and our group has previously demonstrated notable beneficial effects on splanchnic, renal, respiratory and hemo-coagulative functions when intra-aortic balloon pump (IABP)-induced pulsatile perfusion has been employed in routine elective coronary surgery [5][6][7][8]. On the other hand, others did not observe any superiority of pulsatile perfusion with different devices over the traditional linear nonpulsatile CPB [9][10][11].…”
Section: Introductionmentioning
confidence: 99%
“…Serraino et al [14] zeigten zudem im Jahr 2012, dass unter Verwendung eines pulsatilen kardiopulmonalen Bypasses die endotheliale Aktivierung und damit die Ausbildung einer postoperativen inflammatorischen Reaktion vermindert wurde. Die Kontroverse hinsichtlich pulsatil oder nichtpulsatil zeigt sich in Veröf-fentlichungen von anderen Arbeitsgruppen, die keinen signifikanten Unterschied zwischen beiden Perfusionsarten sehen [3,8,10].…”
Section: Diskussionunclassified
“…The ischemia increases expression of paracrine mechanisms for mediating angiogenesis and regeneration of ischemic skeletal muscles (32). Moreover, the influence of different endothelial-derived vasoactive substances such as prostacyclin (15) liberated into damaged muscles results from an alter ation of endothelial structures. These events rapidly lead to invasion of the damaged sites by macrophages, granu locytes, and perfused myoblasts.…”
Section: Morphological Evaluation After Extracorporeal Circulationmentioning
confidence: 99%